Applying the MSMLP model in advancing language teaching and learning: a longitudinal case study on soft skills development - Elleuch, Dalia (Frontiers in Education, 2024)
Language is a dynamic phenomenon that transcends mere verbal expression. In the educational setting, and particularly language teaching and learning, understanding the processes that underlie communication is crucial for effective pedagogy. The Multi-Stratal Model of Language Processing (MSMLP) (Elleuch, 2024) emerges as a neurolinguistic framework that not only dissects the complexities of language processing but also offers a multifaceted perspective through which language education can be advanced, moving beyond traditional linguistic boundaries by integrating social, cultural, emotional, gestural, and linguistic components. The study unfolds by examining the foundational linguistic strata, emphasizing the integration of pragmatics, morphosyntax, semantics, and phonology into a more holistic language curriculum. Social dimensions, encompassing sociolinguistic variables, social context, and conversation analysis, are explored, guiding educators to incorporate these elements into their teaching methodologies. The longitudinal case study focuses on soft skills development among first-year English students at the Faculty of Arts and Humanities in Sfax, emphasizing real-world scenarios and comprehensive assessments. The iterative approach assesses the curriculum's impact on students' soft skills, highlighting MSMLP's applicability in language teaching and curriculum design. The study advocates for embracing the MSMLP, fostering a holistic language teaching approach to prepare students for effective communication in diverse real-world contexts, and unraveling the profound connection between language and the expression of thoughts and feelings beyond explicit verbalization.